2022
DOI: 10.1038/s41467-022-32709-y
|View full text |Cite
|
Sign up to set email alerts
|

NODULIN HOMEOBOX is required for heterochromatin homeostasis in Arabidopsis

Abstract: Arabidopsis NODULIN HOMEOBOX (NDX) is a nuclear protein described as a regulator of specific euchromatic genes within transcriptionally active chromosome arms. Here we show that NDX is primarily a heterochromatin regulator that functions in pericentromeric regions to control siRNA production and non-CG methylation. Most NDX binding sites coincide with pericentromeric het-siRNA loci that mediate transposon silencing, and are antagonistic with R-loop structures that are prevalent in euchromatic chromosomal arms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…3b–d . (2) The transcriptomes of inflorescence and seedlings 6 , 16 were compared in Col-0 (control) samples (Fig. 4a ), identifying 5555 (17.37%) up- and 5618 (17.56%) downregulated genes in flowers relative to seedlings.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…3b–d . (2) The transcriptomes of inflorescence and seedlings 6 , 16 were compared in Col-0 (control) samples (Fig. 4a ), identifying 5555 (17.37%) up- and 5618 (17.56%) downregulated genes in flowers relative to seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis identified specific sets of genes differentially expressed in ndx1-4 , as well as noncoding heterochromatic siRNA (het-siRNA) loci whose activity was significantly changed in the absence of NDX. Transcriptomic data obtained from inflorescence were also compared with previously published seedling data 6 , highlighting development-specific changes in gene expression profiles.
Fig.
…”
Section: Background and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…In rice experiments based on H3K4me3 chromatin‐associated RNA–DNA interactions followed by paired‐end‐tag sequencing (ChRD‐PET) and ssDRIP‐seq analysis, ~20% of H3K4me3‐associated DNA–RNA interactions were shown to be derived from R‐loops, suggesting that R‐loops are involved in chromatin loop conformations (Figure 3C) (Xiao et al, 2022). Recently, work by Karanyi et al (2022) demonstrated that AtNDX, an R‐loop regulator at the FLC locus, regulated heterochromatin organization (Karanyi et al, 2022). However, it is still unclear whether AtNDX‐mediated (hetero)chromosomal contacts in Arabidopsis are R‐loop dependent, as R‐loop structures were shown to be critical for the integrity of topologically associated domains (TADs) in acute myeloid leukemia (AML) cells (Luo et al, 2022).…”
Section: The Biological Significances Of Plant R‐loopsmentioning
confidence: 99%